PENINGKATAN MOTIVASI DAN KETERAMPILAN MEMBACA AKSARA JAWA MELALUI KOCIL AJA (KOMIK CILIK AKSARA JAWA) PADA SISWA KELAS V SEKOLAH DASAR - Adhy Putri Rilianti; Saryanto Saryanto; Ardy Fajar S. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This aim’s research is to increase motivation and Java’s reading skill at fifthgrade student in Suryowijayan Government Elementary School, Yogyakarta.The research method is class action research. Its subject is all students atfifth grade in Suryowijayan Government Elementary School, Yogyakarta. They are22 students. This research activities are planning, doing, observing, evaluating,reflecting, and conclution decision.From pretest and preobservation, students motivation is low. The readingskill in Java’s font rate value is only 30. In fact, minimum standard value is 55.This research is held by 2 cycles. Reflection of cycle 1 result by media Kocil Aja“Aku Telat” is increasing of motivation and reading skill in Java’s font. Thisincreasing is showed at 68% students who have high attention and spirit to study.Rate value of reading skill is 54. Cycle 2 is held by media Kocil Aja “Ardhi lanDhanar”. The result is increasing of motivation and reading skill in Java’s font.There is 91% students who have high motivation and spirit to study. The ratevalue is also increase, it became 55. This value is passed the standard. Based onthis result, media Kocil Aja can increase the motivation and reading skill in Java’sfont at fifth grade students in Suryowijayan Government Elementary School,Yogyakarta.Keyword: Motivation, reading skill, Kocil Aja